Integration of Batik in Science Learning to Overcome Students' Low Critical Thinking Skills in Junior High School: Teacher's Perspective - Zuniari, Nurul Iqdami; Wiyarsi, Antuni; Wilujeng, Insih; Rahmawati, Laifa (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2025)
This study aims to review materials that are difficult for students to develop critical thinking skills, appropriate learning models to improve critical thinking skills, and effective learning approaches. In addition, it is necessary to review the development of teaching materials that integrate local wisdom and to improve critical thinking skills. The research strategy used is qualitative descriptive with a case study research strategy with purposive sampling techniques and using thematic analysis methods. This study shows the low critical thinking skills of junior high school students in science learning, especially in abstract materials such as temperature, heat, and expansion. The integration of local wisdom, such as the batik process, through interactive e-books equipped with videos, animations, and quizzes, as well as discovery learning models, can improve students' understanding and critical thinking skills in a contextual and engaging manner. This innovation is a solution to the challenges of learning science and developing student competencies.